A framework for sustainable supplier selection with transportation criteria. Issue 2 (3rd March 2020) - Roy, Saikat Anjan; Ali, Syed Mithun; Kabir, Golam; Enayet, Rafid; Suhi, Saima Ahmed; Haque, Tasmiah; Hasan, Rifat
ABSTRACT: Appropriate suppliers are essential for optimizing cost in contemporary supply chain decisions. Supplier selection is a challenging issue that requires the evaluation of both quantitative and qualitative criteria based on imprecise and limited information. This study proposes a framework to assess sustainable supplier selection methods using a fuzzy analytical hierarchy process (FAHP) and the preference ranking organization method for enrichment evaluation (PROMETHEE). Based on a literature review and expert opinions, 20 sustainable supplier selection criteria were grouped into economic, environmental, social, and transportation dimensions. FAHP was then used to determine the weights of the criteria and PROMETHEE was used to rank the suppliers. The proposed framework was implemented in a ready-made garment company in Bangladesh. The findings showed that 'price of product, ' 'profit on product, ' 'quality of product, ' 'environmental management system, ' and 'green packaging and labeling' were the top five sustainable supplier selection criteria. Business professionals and managers will benefit from this study when identifying suppliers to ensure sustainability in the supply chain.